Perception of Stakeholders Towards Attributes of the Penang National Park as a Nature Tourist Destination - Ariffin, Suhaila (2008)
The growth of the tourism industry in Malaysia has resulted in an increasing number of tourist visits to the natural areas. A series of studies are conducted to thoroughly identify the perceptual attributes of a nature tourism destination of Penang National Park. The attributes consist of natural environment, recreational activities, park management and socio-cultural traits that exist at and surrounding the park. The purpose of the study is to establish the perceptions of the three main stakeholders of Penang National Park on the respective attributes selected for this study. The stakeholders are visitors, local villagers and park personnel of Penang National Park. Three different sets of questionnaire survey instruments are used to assess the perceptions of each stakeholder group. However, this study is focused on the visitors because they are the users and the consumers of the products at Penang National Park. T-test and ANOVA show the differences in the perceptions of visitors on the attributes selected for the park. The findings show that the majority of the stakeholders are satisfied with the attributes available at Penang National Park. The main implication of the different perceptions of visitors toward the attributes at the park is that park management should improve their efforts in order to fulfil the needs of the different characteristics of visitors. The management should sustain the quality of services and carry out only environmental-friendly development to maintain nature tourism in Penang National Park. The management practices should be in tandem with the principles of nature conservation of national parks.